Everyday Inclusion with Immigrant and Racialized Youth in Public Libraries - Crossman, Katie; Ibrahim, Eman H.; Wang, Haimei; Kitchen, Carrie; Banting, Lindsay (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
This qualitative study explores the lived experiences of racialized and immigrant youth in public libraries, focusing on a sense of belonging. The research team conducted 18 observations, two focus groups, surveys (n=79), and interviews (n=17). Findings were then explored with a co-design team of seven racialized youths. Data analysis identified four key themes influencing belonging: accessibility, safety, inclusion (subthemes: familiarity, representation, and acceptance), and agency. Findings reveal that youth value safe, familiar, and inclusive environments where they feel represented and accepted. They also highlight challenges such as limited agency and racial discrimination. Ultimately, the findings emphasize the importance of fostering environments where youth are engaged, empowered, and heard so they can help shape public spaces where they feel truly valued. This paper also offers recommendations for ways public libraries can encourage a sense of belonging for immigrant and racialized youth and directions for future research.